Introduction to robotics : mechanics and control - Craig, John J. ([S.l.] : Prentice Hall, 2004)
Now in its third edition, Introduction to Robotics by John J. Craig provides readers with real-world practicality with underlying theory presented. With one half of the material from traditional mechanical engineering material, one fourth control theoretical material, and one fourth computer science, the book covers rigid-body transformations, forward and inverse positional kinematics, velocities and Jacobians of linkages, dynamics, linear control, non-linear control, force control methodologies, mechanical design aspects and programming of robots. For engineers.